Routine Vaccine Simulation for Infants in a Mobile Environment - Asiado, Annabelle Joy C.; Cabuntucan, Sweet Zerlyn Z.; Santiago Jr., Cereneo S. (International Journal of Computing Sciences Research; Vol 6 (2022): Vol 6, 2022)
Purpose – This study aimed to develop and evaluate the Routine Vaccine Simulation for Infants. The routine vaccine simulation application was developed for the health workers and parents to provide basic information and press the importance of the vaccination to infants. Method – The researchers used the fourth-generation technique (4GT) for the software development life cycle of the application. The technique adapted contains four major parts namely, requirements gathering, design strategy, implementation, and testing. Results – The application was tested and evaluated by health workers, parents, and IT practitioners from the academe and the industry. The evaluation was based on criteria for core app quality. Descriptive and inferential statistics were employed for data presentation and interpretation.  As a whole, the evaluation of the android-based routine vaccine simulation application was found excellent in most of its features. The finding asserts the adherence to the standards of android development applications and conforms to the expectations of the app’s potential users. Conclusion – The development of a routine vaccine app for infants serves as a new platform for immunization awareness and education. Once information given in the app is taken earnestly, infants will be protected against diseases. Thus, controversies surrounding vaccination hesitancies can be decreased. Recommendations – A thorough information dissemination and education campaign regarding vaccine safety can be initiated in the local communities to address the issues on vaccine safety and hesitancy. Research Implications – The healthcare system in the communities through the local government unit (LGU) will be able to benchmark and implement the information dissemination and education to mothers and health workers using the app.